Sub-nanosecond terahertz radiation obtained with an aperiodically poled lithium niobate and organic HMQ-TMS - Lee, Seung Heon; Kwon, O. Pil; Carrillo-Fuentes, Miriam; Cudney, Roger S. (Optics Express, 2020)
We report a compact, simple source of terahertz radiation that can be tuned to well-defined frequencies spanning ∼1.4 to 10 THz, based on difference-frequency generation in an HMQ-TMS crystal. The pair of pump pulses required for this process is obtained by optical parametric generation in an aperiodically-poled lithium niobate crystal; the center wavelength of this pair of pulses is around 1.45 µm. We obtained 40 nJ THz pulses using 38 µJ, 0.85 ns pump pulses.
Keywords: Aperiodically poled lithium niobate; Center wavelength; Difference-frequency generation; Optical parametric generation; Pump pulse; Sub nanoseconds; Terahertz radiation; THz pulse